2018
DOI: 10.1038/s41388-018-0442-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of UAP1L1 as a critical factor for protein O-GlcNAcylation and cell proliferation in human hepatoma cells

Abstract: Aged hepatocyte-specific-Mcl-1 knockout (MKO-hep) mice are prone to develop liver tumors mimicking human hepatocellular carcinoma (HCC). Here we reported that a protein named UDP-N-acetylglucosamine pyrophosphorylase-1-like-1 (Uap1l1) is upregulated in the liver of young MKO-hep mice without any macroscopically detectable tumor nodules and is prominently expressed in the hepatic tumors developed in the aged MKO-hep mice. Intriguingly, human UAP1L1 is also significantly upregulated in a distinct subset of HCC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…UAP1L1 (UDP- N -acetylglucosamine pyrophosphorylase 1 like 1) appears to be a regulator of O-GlcNAc transferase function and is a critical factor for cell proliferation in human hepatocarcinoma cells [73]. UAP1L1 is significantly upregulated in a distinct subset of HCC tissues, and patients with upregulated expression of UAP1L1 appeared to have a poor prognosis [73].…”
Section: Resultsmentioning
confidence: 99%
“…UAP1L1 (UDP- N -acetylglucosamine pyrophosphorylase 1 like 1) appears to be a regulator of O-GlcNAc transferase function and is a critical factor for cell proliferation in human hepatocarcinoma cells [73]. UAP1L1 is significantly upregulated in a distinct subset of HCC tissues, and patients with upregulated expression of UAP1L1 appeared to have a poor prognosis [73].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, their investigations further suggested that UAP1 could block the influence of Nlinked glycosylation inhibitor on prostate cancer cells, which could be re-sensitized after silencing UAP1 [31]. UAP1L1 is another protein with 59% sequences identity to UAP1 [32]. The studies of Yang-Yen et al indicated that, despite of the structural similarity between UAP1 and UAP1L1, they possess distinctly different functions in the synthesis of UDP-GlcNAc.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Yang-Yen et al indicated that, despite of the structural similarity between UAP1 and UAP1L1, they possess distinctly different functions in the synthesis of UDP-GlcNAc. Moreover, their studies also demonstrated the overexpression of UAP1L1 in HCC tissues compared with normal tissues and elucidated the promotion or inhibition of HCC development in vitro and in vivo by UAP1L1 overexpression or knockdown [32]. In spite of these, the role of UAP1L1 in human cancers, especially gastric cancer and the underlying mechanism are still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…does not efficiently catalyze UDP-GlcNAc synthesis, but instead interacts directly with the Cterminal catalytic domain of OGT. Knockdown of UAP1L1 markedly reduced global O-GlcNAcylation in HepG2 and TONG cells, yet UAP1L1 alone is not sufficient to bolster OGT activity in vitro [44]. Thus, UAP1L1 likely maintains OGT activity within cells through direct binding, though more detailed characterization is necessary.…”
Section: Post-translational Modificationsmentioning
confidence: 99%
“…UDP-N-acetylglucosamine pyrophosphorylase-1 (UAP1) catalyzes the last step in the synthesis of UDP-GlcNAc. A UAP1 paralog, UAP1-like-1 (UAP1L1), is required for OGT mediated protein O-GlcNAcylation in HepG2 liver hepatocellular carcinoma cells [44]. Surprisingly, UAP1L1…”
Section: Post-translational Modificationsmentioning
confidence: 99%